Yahoo Web Search

  1. Sort by

  1. R=3a^2b Since b is on the right-hand side of the equation, switch the sides so it is on the left-hand side of the equation. 3a^2b=R Divide each term in the equation by 3a^(2). 3a^2b/3a^2=R/3a^2...

    2 Answers · Education & Reference · 16/07/2013

  2. 1) r = 4∙sin(θ) r = 0 for 4∙sin(θ) = 0 sin(θ) = 0 θ = 0 or θ = π r' = 4∙cos(θ) r' = 0 for 4∙cos(θ) = 0 cos...or θ = π 3 + 2∙cos(0) = 5 3 + 2∙cos(π) = -5 so r-max at θ = 0 Graph: http://i48.tinypic.com/doauci...

    1 Answers · Science & Mathematics · 22/05/2012

  3. r/5 + 6/5 = r/7 + 8/7 7r + 42 = 5r + 40 2r = - 2 r = - 1 Answer: r = - 1 Checking: - 1/5 + 6/5 = - 1/7 + 8/7 5/5 = 7/7 1 = 1

    2 Answers · Science & Mathematics · 17/11/2010

  4. R(x) = -2x³ - 7x + 14 R(11) = -2(11)³ - 7(11) + 14 R(11) = -2(1331) - 77 + 14 R(11) = -2662 - 77 + 14 R(11) = -2725

    3 Answers · Science & Mathematics · 03/07/2008

  5. I = e/R + r IR = e + rR {multiply both sides by R} IR - rR = e {subtract rR from both sides} (I - r)R = e {factor left side} R = e/(I - r) {divide both sidea by (I - r)

    4 Answers · Science & Mathematics · 13/10/2007

  6. f(r) = |(r - 2)(r - 1)|. As a piecewise defined function f(r) = (r - 2)(r - 1) if r ≤ 1 or r ≥ 2 f(r) = -(r - 2... that f ' isn't defined at r = 1. f has three critical values on the...

    1 Answers · Science & Mathematics · 27/06/2013

  7. lim ((a^r + b^r)/2)^(1/r) (as r --> 0) LN lim = lim LN lim LN ((a^r + b^r)/2)^(1/r) = = lim (1/r)LN ((a^r + b^r)/2) (as r --> 0) is...

    3 Answers · Science & Mathematics · 15/10/2012

  8. 1) Let L = {r in R| ra = 0}. a) If u and v are in L then (u+v)a...b) If r is in R and u is in L then (ru)a = r(ua) = 0, so ru is in L, which shows that L is...

    1 Answers · Science & Mathematics · 22/12/2010

  9. Complete the square r^2 + 3r = 2 (r + 3/2)^2 - 9/4 = 2 (r + 3/2)^2 = 2 + 9/4 (r + 3/2)^2 = 17/4 r + 3/2 = +/- Sqrt 17/4 r = - 3/2 +/- Sqrt 17/4 If you need to go further r = - 3/2 + 2.0615 = 0.5615 r = - 3/2 - 2.0615 = - 3.5615

    1 Answers · Science & Mathematics · 16/08/2010

  10. π(r+6) ² = 15(2πr) + 2 πr² First, recognize that since everything on both... out of the equation entirely. π(r+6) ² = 15(2πr) + 2 πr² π(r+6) ² = π[15(2r) + 2r²] (r+6...

    5 Answers · Education & Reference · 20/09/2010

  1. Try asking your question on Yahoo Answers